The Effect of Triangle Slope Variation on Froude Number with Numerical Simulation - Mukhsan Putra Hatta; Ira Widyastuti; Andi Muh. M. Makkarumpa’ (Salehan Institute of Higher Education, 2023)
Many parameters can be influenced by speed flow, like form resistance and speed flow. Form obstacles influence structure turbulent flowing water, so that can raise potency change speed and pattern flow around the structure building. This study considers the tilted corner prisoner structure triangle and incoming water flow to influence the pattern and speed flow that occur after the genre through the obstacle triangle using IRic simulation. IRIC is a simulation platform that supports numeric and various breaker computing problems in water science and engineering. The variations of the corner prisoner plate triangle used in this study are 30°, 45°, and 60°. The transverse channel is blocked with a ratio of β = 1/10, and upstream-downstream boundary conditions are open. Results show what will happen in the genre critical moment pass structure. Because the change is significant, Froude's number. Observations that took place showed that speed flow on each slope was stable before the pass structure and was not stable after the pass structure. Whirlpools occur on a45° slope, so the speed flow that occurs will increase significantly. On an incline of60°, it will have the largest Froude number, which is caused by the depth (D)created by the 60°angle being higher in comparison with another slope. For an incline of30°, show speed, more flow, and a constant flow with a bigger Froude number. Doi: 10.28991/CEJ-2023-09-12-012 Full Text: PDF